Meat yield of grazing river buffalos (Bubalus bubalis) - Fundora, Orlando; Fernández, D.; Sánchez, Lyhen; González, María E. (Cuban Journal of Agricultural Science, 2016)
In order to determine grazing river buffalos meat yield, 40 river buffalos (20 Buffalypso and 20 Carabao), with final liveweights of 412.0 and 394.2 kg, started with 170 and 184 kg, respectively, were used. These animals were grazing in an area of 77ha, divided into four paddocks composed by Dichantium annulatum, Digitaria decumbens, Dichantium caricosum, Bothriochloa pertusa, Paspalum notatum and Mimosa pudica, which constituted 95.6% y 87% of the botanical composition, and available dry matter yield of 2.2 t.ha-1 and 0.8 t.ha-1 during rainy or dry periods, respectively. Meat yield, bromatological composition and some physical properties were determined. Total meat yield per surface unit was higher in Buffalypso (72 kg) than in Carabao (62 kg). In addition, weight proportion of hindquarters regarding carcass was higher (P < 0.001) in Buffalypso (50.6%), compared to Carabao (48.8 %), but this did not affect yield of first quality meat in carcass (17.5 vs. 17.1%, respectively). Likewise, short loin proportion regarding total first quality meat (15.0 and 14.2 %) wassuperior (P < 0.05) in Buffalypso. However, proportions of inside round (22.3 and 23.1%) and tenderloin (6.9 and 7.5%) were lower (P < 0.05 and P < 0.01) in this breed. It can be concluded that total and first quality meat is similar in both breeds, although they showed different proportions in forequarters and hindquarters, and in cuts of first quality meat, while the yield of total meat per surface unit is superior in Buffalypso breed.Key words: river buffalos, meat, yield, composition